The Implementation of the Pan-Indian Form on the Keralan Ground: A.R. Rajaraja Varma’s Citranakṣatramālā - Hermina Cielas (Cracow Indological Studies, 2016)
In the 19th century Keralan literature contrasts between the traditional approach and a modern way of writing, as well as the attempts to reconcile those two modes, were particularly visible. The group of Kodungallur (Kōṭuṅgallūr) poets acted against over-Sanskritization in Malayalam poetry, while in the nearby Travancore (Tiruvitāṅkūr) poets advocated Sanskrit and tried to emulate classical forms. A. R. Rajaraja Varma (1863–1918), being one of the leading figures of the Travancore progressive movement, combined traditional, modern and local forms and themes in his works. He mastered the usage of well-known elements of kāvya literature in the description of events of his time. One of the examples that joins all of these factors is Citranakṣatramālā, a short composition written by seventeen-year-old author in honour of his patron—Maharaja Visakham Tirunal (Viśākham Tirunāḷ Mahārāja) of Travancore. The analysis of selected passages of the work reveals Rajaraja Varma’s ability to implement pan-Indian form on local ground successfully.